2008
DOI: 10.1182/blood-2007-08-107698
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytes do not express but acquire monocyte-derived tissue factor in whole blood: evidence for a direct transfer

Abstract: Unlike unanimous opinion on tissue factor (TF) expression in monocytes, the quest for TF presence in granulocytes has been going on for decades. To study the cell origin and track the blood-borne TF, we assessed TF activity and protein levels, knocked-down endogenous TF expression with small interfering RNA (siRNA), and overexpressed TF-yellow fluorescent protein (TF-YFP) fusion in immunologically isolated human monocytes and granulocytes. Monocytes and, to a much lesser extent, granulocytes isolated from lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 35 publications
7
76
0
2
Order By: Relevance
“…This is in agreement with our previous studies, in which we clearly showed that neutrophils or eosinophils do not synthesize or express TF activity when blood has been exposed to various forms of activation [6,7]. This, however, is a controversial subject, as there are some reports of TF expression by granulocytes [10].…”
supporting
confidence: 93%
“…This is in agreement with our previous studies, in which we clearly showed that neutrophils or eosinophils do not synthesize or express TF activity when blood has been exposed to various forms of activation [6,7]. This, however, is a controversial subject, as there are some reports of TF expression by granulocytes [10].…”
supporting
confidence: 93%
“…2,3 Clinical studies have shown that traditional vascular risk factors are associated with leukocyte activation and may predispose to thrombogenesis. 4,5 PMNs may contribute to fibrin generation directly by exposing active tissue factor (TF) 6 and/or indirectly by inactivating the major TF inhibitor, TF pathway inhibitor (TFPI). 2 PMNs may also locally assemble proteins of the factor XII-driven contact pathway.…”
Section: Introductionmentioning
confidence: 99%
“…41 It is possible, as previously suggested, that TF was transferred from monocytes or monocyte-derived microparticles to PMNs. 6 Massberg et al have recently shown that blood -activated neutrophils can inactivate TFPI via the release of proteases at the site of injury. 2 In this model, the subendothelial matrix is exposed to blood leading to the formation of a platelet thrombus.…”
mentioning
confidence: 99%
“…48 TFϩ MonoMPs constitute the second largest pool of thrombogenic MPs after plateletderived MPs (PMPs). 49 -51 TFϩ MonoMPs can interact with neutrophils, 52 transferring to them a procoagulant activity. Indeed, neutrophils are capable of fusion with MPs derived from other cell types.…”
Section: Monocytes and Monocyte-derived Mpsmentioning
confidence: 99%